Pengembangan Media Teka Teki Silang "ASEAN" pada Pembelajaran IPS di Sekolah Dasar - Ummi Khoirun Nisa; Erik Aditya Ismaya (Journal on Education, 2024)
The unimaginative use of learning media and the lack of development and variation in the creation of learning media, especially in friendship exam learning content, has resulted in a decline in student interest and learning outcomes. Therefore, we need a medium that can be used to help make it happen so that it can run perfectly. This exploration aims to make learning media a crossword puzzle for the social exam learning content for class V elementary schools. The method used in this research is a literature review. From the article data obtained in the form of articles discussing the development of learning media using the ADDIE model, all of them are quoted and filtered. Again, look for those that suit your needs. From the results of reviews from several sources, the sharp crossword puzzle learning media for the learning content of the fifth grade elementary school social test was successfully created. using the ADDIE model stages. Crossword learning media can help students understand the material and subsequently improve student learning outcomes. This can happen because the clever crossword puzzle learning media has been tested for the correctness of the questions and their suitability. This learning media is generally used by students in synthetic learning because the results of the investigation have good capabilities, and based on the feasibility test, the post-test results are higher than the pre-test, this shows how good this media is. can also improve student learning outcomes, especially in the learning content of Grade V Elementary School. Thus, the learning media for intuitive crossword puzzles in friendship learning exams is important and effective for use in learning exercises because it can develop more student learning outcomes. The use of this exam is that it can convince experts to have the option to develop and be creative in learning.